Monitoring System for Physical Water Quality Parameters and Automatic Control for Chlorine Dosing in a Aerator Treatment Plant - Balarezo, Juan (2021)
This work proposes the development and creation of an automatic monitoring and control system for the dosage of chlorine in the water treatment plant, purifying the vital liquid and avoiding the distribution and consumption of water contaminated by microorganisms. This is achieved by monitoring the physical parameters through the data sent by wireless sensors, acquiring them in a database, sending the data in real time to a web server, where they can be visible to the public, and generating automatic control in Based on the data obtained, this occurs in a water treatment pools. For this, a Raspberry Pi board is used, it acts as a data store, two Arduino Mega, acting as control nodes, a LAN server, and a PID control for the automatic control of chlorine dosage, thus achieving precautionary that the water is disinfected from any microorganism present